Simulation-based training improves ITU staff knowledge in the management of head injuries. - Smith, Matthew (BMJ Qual Improv Rep, 2014)
Traumatic brain injury (TBI) in the polytrauma situation is a phenomenon often seen at UK hospitals. Without immediate access to dedicated neurocritical care facilities, the potential for under-treatment of the underlying brain injury and serious neurological sequalae is high, especially if staff on the general intensive care units on which these patients are treated lack confidence in this area of practice, a reality confirmed by our baseline study. We found that by engaging staff by implementing a regular simulation-based team training programme, we were able to boost the skills, knowledge, and ultimately confidence levels in treating TBI amongst these groups of staff. “Buy-in” by those concerned was high, and we found that self-reported scores for the attributes described above were improved considerably and consistently by our intervention. This quality improvement project has been rolled out through several iterations to become sustainable, has significant cost-saving potential, and will hopefully lead to proven improved clinical outcomes for this group of patients.